Environment, Trauma and Technical Innovations: Three Links Between Donald W. Winnicott and Sándor Ferenczi (2017)
Throughout this paper, the theoretical and clinical approaches of D.W. Winnicott are reviewed in order to reread the written production of Sándor Ferenczi. Winnicott's clinical and theoretical concepts allow returning to Ferenczi and rescuing aspects of his work that had been silenced in the psychoanalytic community. Ferenczi, in turn, is one that holds his presence in Winnicott's thought. Even though there are few times in which he cites Ferenczi in his work, it is possible to draw clear relationships between both theories. Three main issues are addressed: the role of the environment as active; the primitive traumatic event in which there is no one that has experience of it, and psychoanalysis as the place to experience that which happened in the first months of life for the first time; and, finally, severe pathologies and psychoses: technical innovations in Winnicott and Ferenczi for the treatment of psychotic and borderline patients. It is concluded that the theoretical and technical developments of Winnicott serve to illuminate a retrospective reading of Ferenczi. © 2016 Asociación Colombiana de Psiquiatría